2000
DOI: 10.1086/303399
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution of Seed Oils in Plants: Accounting for the Biogeographic Distribution of Saturated and Unsaturated Fatty Acids in Seed Oils

Abstract: Structural, energetic, biochemical, and ecological information suggests that germination temperature is an important selective agent causing seed oils of higher-latitude plants to have proportionately more unsaturated fatty acids than lower-latitude plants. Germination temperature is predicted to select relative proportions of saturated and unsaturated fatty acids in seed oils that optimize the total energy stores in a seed and the rate of energy production during germination. Saturated fatty acids store more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 65 publications
10
117
3
Order By: Relevance
“…Thus, the significant lower oil content of seed from Santa Elena compared to seeds from all other locations could be related, at least partially, to the altitude differences between locations of production. Warm temperatures generally increase the level of saturation of chia fatty acids, like for other oil seed crops [16,19,23,24]. However, the variation in a-linolenic fatty acid, as was found herein, could not be fully explained by the negative relationship between land elevation and oil desaturation levels.…”
Section: Discussionmentioning
confidence: 38%
“…Thus, the significant lower oil content of seed from Santa Elena compared to seeds from all other locations could be related, at least partially, to the altitude differences between locations of production. Warm temperatures generally increase the level of saturation of chia fatty acids, like for other oil seed crops [16,19,23,24]. However, the variation in a-linolenic fatty acid, as was found herein, could not be fully explained by the negative relationship between land elevation and oil desaturation levels.…”
Section: Discussionmentioning
confidence: 38%
“…The germination temperature is an important selective factor causing seed oils of plants native to high latitudes or altitudes to have a greater proportion of unsaturated fatty acids (Linder 2000 ) . The explanation is that in cold environments the catabolism of unsaturated fatty acids is more likely than that of saturated ones, and the seeds germinate and grow faster at lower temperatures, increasing their adequacy, even at the cost of a lower total energy available to the embryo.…”
Section: Variation In the Content And Composition Of Seed Oilmentioning
confidence: 99%
“…However, it is surprising how little attention has been given to the selection factors that drive the evolution of the fatty acid composition of seeds. In this regard, Linder 49 suggested that the temperature of germination is an important selective agent that causes the seed oils of plants native to high latitudes or altitudes to have a higher proportion of unsaturated fatty acids that plants in lower latitudes/altitudes. The explanation is that in cooler environments high latitudes and altitudes the catabolism of unsaturated fatty acids is more feasible compared to saturated, thus the seeds with more unsaturated fatty acids germinate and grow faster at lower temperatures, increasing their fi tness, even at the expense of having less total energy available.…”
Section: Pattern In the Fatty Acid Compositionmentioning
confidence: 99%